Jök 2019
DOI: 10.33799/jokull2019.69.103
|View full text |Cite
|
Sign up to set email alerts
|

Perennial snow patch detection based on remote sensing data on Tröllaskagi Peninsula, northern Iceland

Abstract: The understanding of permafrost distribution in Iceland is still limited and current knowledge is mainly based on small scale observations and regional modelling using temperature data. In the Alps Perennial Snow Patches have been considered to protect permafrost from solar radiation and are used as an indicator for the occurrence of local permafrost. In this study perennial snow fields are detected and classified based on aerial and satellite images. Effects of climatic and topographic factors on the snow fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A field survey in the Snowy Mountains of Australia [14] found that winter snowfall, wind direction and summer warmth all influenced snow patch duration. An Icelandic satellite survey [13] also showed winter snowfall and mean annual temperature to be important factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A field survey in the Snowy Mountains of Australia [14] found that winter snowfall, wind direction and summer warmth all influenced snow patch duration. An Icelandic satellite survey [13] also showed winter snowfall and mean annual temperature to be important factors.…”
Section: Discussionmentioning
confidence: 99%
“…Perennial snow patches are a widespread feature of montane and arctic landscapes worldwide, and recent years have seen studies on this feature in Scotland [11], the Canadian arctic [12], Iceland [13], Australia [14] and Scandinavia [15]. Snow patch duration and survival is related to climatic factors such as winter snowfall and seasonal temperatures [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Andrés et al 2016). Perennial snow patches (Tussetschläger et al 2020), active rock glaciers and stable ice-cored moraines are abundant in the region (Farbrot et al 2007a;Lilleøren et al 2013), with the latter two being used to calibrate numerical models of mountain permafrost (Farbrot et al 2007b;Etzelmüller et al 2007). The lower mountain permafrost limits in Tröllaskagi have been modelled at 600-900 m a.s.l.…”
Section: Settings Of the Case Studiesmentioning
confidence: 99%